Structural, optical and photocatalytic applications of biosynthesized NiO nanocrystals. Issue 2 (3rd April 2018) - Diallo, A.; Kaviyarasu, K.; Ndiaye, S.; Mothudi, B. M.; Ishaq, A.; Rajendran, V.; Maaza, M.
ABSTRACT: NiO is one of the most important candidates for semiconductors metal oxide nanocrystals by the arrangement of photocatalytic application. However, the photocatalytic performance of biosynthesized nanocrystals using Aspalathus linearis (Burm.f.) R. Dahlgren has not been investigated yet. In this contribution, we synthesize α -Ni(OH)2 using an A. linearis . A heat treatment of the α -Ni(OH)2 is carried out at 300–400°C for 2 h at normal air yields. Furthermore, we have characterized the structural, optical and photocatalytic activity of the samples. The optical results indicate that biosynthesized nanocrystals exhibit UV–visible light absorption and a narrow range distribution of intense green light (518.95 nm) emission, which decreases significantly as annealing temperature increases. The bandgap energies of the sample annealed at 300–400°C shift to lower photon energy, compared to bulk NiO (∼ 4 eV). Moreover, the photocatalytic experimental results reveal that NiO nanocrystals enable color switching of methylene blue. GRAPHICAL ABSTRACT: